Helt fremme i integrationsskoene - en klassiker fylder rundt - Bach, Tine (Rambam. Tidsskrift for jødisk kultur og forskning, 2012)
Acting for Immigration. A Classic Celebrates its 100th Birthday 100 years ago, the play Indenfor Murene (Inside the Walls) by Henri Nathansen premiered at the Royal Danish Theatre. Since then, the play has been set up several times but has not lost its relevance. Henri Nathansen was born in 1868 and died in 1944. He grew up in Hjørring as one of the only Jews in the town. He felt great sympathy for the new East European Jews, who at that time immigrated to Denmark in large numbers. Especially their difficulties in being accepted in the Danish Jewish community had his interest. This might be the reason why his authorship often deals with this topic. In his work, he often flirts with the idea of breaking borders between the Christian and the Jewish world and, in addition, to create a greater community which includes more than just Judaism. This is one theme in Indenfor Murene. The play is a love story between a Jewish woman and a Christian man and the difficulties they meet within their families because of their love for each other. The theme was very controversial at the time the play premiered. Today, it is not unusual that a Jew would marry a non-Jew, but the theme is still current. It is not unlikely that parents in some families would feel the same way today as the parents do in Indenfor Murene. An example is the French film Bad Faith, which is a love story between a Muslim and a Jew. The question of integration and how a minority group can be accepted into a community is also very current today.